Study on characteristics of acacia wood by FTIR and thermogrametric analysis - Viet, Dinh Quoc; Son Tho, Van Dinh (Vietnam Journal of Chemistry, 2017)
Renewable energy is very important for future development of society. Biomass is a type of energy that can be renewable. In this study, characterization of acacia wood is focused and discussed. The functional groups, crosslinking in the biomass structures and thermal decomposition were mentioned. In that, functional groups, crosslinking of acacia wood are analyzed by Fourier transform infrared spectroscopy and thermal decomposition is investigated with thermogravimetric equipment. Acacia wood has typical group of wood from FT-IR such as O-H, C-H, C-O, C-O-C of cellulose and lignin. The structure of cellulose is also very easy to be broken by thermal factor. In the inert atmosphere, cellulose decomposed dramatically in the temperature range of 280 to 550 °C and degradation of lignin occurred in the temperature range of 100 to 800 °C. Acacia wood decomposed in the temperature range of 200 to 580 °C with three distinct weight loss stages. The first stage is water removal of biomass and it completes below 120 oC. The second stage is in the range of 200-350 oC that is the initial decomposition of biomass and directly related to the formation of volatile substances from decomposition of hemicellulose and cellulose. The last stage is the continuous decomposition of lignin at higher temperature up to 580 oC. For cellulose, the thermal degradation in air atmosphere has decomposition temperature higher than that in the nitrogen atmosphere but the ending temperature is lower. On the other hand, the thermal decomposition of lignin just occurred from 150 to 560 oC. The reaction for acacia wood demonstrated three stages. The water evaporated at lower than 120 oC in the first stage. The second stage is the devolatilization of biomass (214-322 oC) and the third one (322-420 oC) is the combustion of char. Keywords. Biomass, acacia wood, cellulose and lignin, FT-IR, characterization of biomass